Simultaneous dual true random numbers generator (2016)
This paper details the design and implementation of a simultaneous dual true random numbers generator using only one laser and a digital signal processing system with a DE0 Nano FPGA. We implemented the random generator in such a way that a vacuum optical field will exist in our system. Taking advantage of the inherently random nature of the field, simultaneously quadrature components are measured in order to generate a truly random voltage signal. Also, we used a dynamical system of statistical analysis to eliminate any residual component of direct current on output voltage signal due to an (unavoidable) optical power imbalance in the optical system that was implemented. Finally, were measured the parameters of the auto-correlation and bias probability with values of 0.00010, 0002, respectively, which means that our system can be considered as a true random sequence generator capable of producing two sequences in an independent manner with a bit rate of up to 25 MHz.